Legalising the Unlawful? A Critical Legal Analysis of Reclamation Without Permit under Indonesia’s Maritime and Spatial Planning Law - Amaliyah Amaliyah; Muhammad Tizar Adhiyatma; Sitti Nurlin (Varied Knowledge Journal, 2026)
The authorisation of Management Rights over reclaimed land without obtaining proper permits, as permitted under Government Regulation Number 18 of 2021 (the Land Registration Regulation), has engendered conflicts with Indonesia’s higher statutory laws, specifically Law Number 32 of 2009, Law Number 27 of 2007, and Law Number 17 of 2008. This inconsistency within the regulatory framework undermines the precautionary principle, jeopardises legal certainty, and tacitly condones illegal reclamation activities, thereby contravening the doctrine of ex injuria jus non oritur. This research employs a normative and conceptual legal methodology, analysing the development and coherence of statutory norms through doctrinal interpretation. The purpose of this study is to critically evaluate the legality of granting land rights over unauthorised reclamation under Indonesian law and to examine the regulatory discord arising from conflicting legal norms. The findings suggest that the Land Registration Regulation deviates from the hierarchical structure of legislation, thereby creating legal loopholes that compromise environmental governance and procedural justice. The study concludes that Indonesia must reform its regulatory framework to harmonise environmental, spatial, and land laws, thereby strengthening the rule of law, preventing normative fragmentation, and promoting sustainable coastal management.